2020
DOI: 10.1200/jco.19.02953
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Comparative Clinical Studies in the Development of Oncology Biosimilars

Abstract: Biosimilars have the potential to broaden patient access to biologics and provide cost savings for health care systems. During the development of a biosimilar, data that directly compare the proposed biosimilar with the reference product are required. Such comparative data are generated in a stepwise hierarchical process that begins with extensive laboratory-based structural analyses and functional assays. This initial analytical phase serves as the foundation for the demonstration of biosimilarity and is foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
0
28
0
3
Order By: Relevance
“…Based on the totality of the evidence, which includes sophisticated analytic and clinical assessments, approved biosimilars of trastuzumab, such as SB3, have the potential to increase accessibility to trastuzumab-based therapy without compromising efficacy or safety [ 13 , 15 , 27 , 30 , 38 , 41 , 44 ]. Furthermore, although the phase III study of SB3 in patients with early HER2 + breast cancer was not designed to detect a relationship between ADCC and clinical outcomes, and survival results by exposure to ADCC drift were derived from a post hoc analysis, the SB3 development process has provided some evidence to support the hypothesis of a relationship between ADCC activity and long-term survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the totality of the evidence, which includes sophisticated analytic and clinical assessments, approved biosimilars of trastuzumab, such as SB3, have the potential to increase accessibility to trastuzumab-based therapy without compromising efficacy or safety [ 13 , 15 , 27 , 30 , 38 , 41 , 44 ]. Furthermore, although the phase III study of SB3 in patients with early HER2 + breast cancer was not designed to detect a relationship between ADCC and clinical outcomes, and survival results by exposure to ADCC drift were derived from a post hoc analysis, the SB3 development process has provided some evidence to support the hypothesis of a relationship between ADCC activity and long-term survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A proposed biosimilar cannot be superior to its reference product [ 23 , 40 , 46 ], but in the ABP 980 and SB3 phase III equivalence studies, it was observed that pCR rates were lower in patients treated with drifted batches of the trastuzumab reference product than those treated with the pre-drifted trastuzumab reference product or biosimilar trastuzumab [ 42 , 43 ]. As described in European Public Assessment Reports for SB3 and ABP 980 [ 42 , 43 ], it has been acknowledged that the downward drifts in ADCC activity in some of the trastuzumab reference product batches used in these studies could have at least partially confounded the results by contributing to the observed differences in pCR rates between treatment arms and their relatively high upper CI limits [ 13 , 15 ]. Taking totality of evidence into account, SB3 and ABP 980 were therefore considered comparable, rather than superior, to the reference product, and approved as biosimilars of trastuzumab [ 15 , 42 , 43 , 45 ].…”
Section: Importance Of Biologics Quality In Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…During the development of a biosimilar, data that directly compare the proposed biosimilar with the reference product are required. These comparative data are generated in a stepwise hierarchical process from extensive laboratory-based structural analyses and functional assays, to clinical safety and efficacy (24). Demonstration of similarity in these trials, along with extensive evidence of similarity from other tests, allows the extrapolation of data with the reference compound to the biosimilar in other non-tested indications (25).…”
Section: Introductionmentioning
confidence: 99%